Implementing Mobile Portfolio Application in EFL Classes: Efficiency for Fostering Reflective Thinking, Directed Motivational Currents (DMCs), and Cognitive Learning - Fatemeh Gandomkar; Afsaneh Ghanizadeh; Safoura Jahedizade; Kiana Hosseinion (Journal of Modern Research in English Language Studies)
Today, traditional passive learning and note taking are less effective for students adapting to modern life skills. Mobile portfolios, versatile learning tools with numerous benefits, are finding their way into educational domain in promoting active learning. This study explored the impact of the present researchers’ designed mobile portfolio (called Class Mass) on students’ reflective thinking, directed motivational currents (DMCs), and cognitive learning. This study was performed in two ninthgrade English classes of a state-run female junior high school via a quasiexperimental research design. In terms of instruments, the following scales were utilized: reflective thinking inventory (measuring four distinct components), DMC disposition questionnaire, and cognitive learning scale. The results of independent samples t-test and multivariate analysis of variance (MANOVA) demonstrated the effectiveness of using the mobile portfolio application on learners’ three components of reflective thinking, DMCs, and cognitive learning. The study suggests that teachers should recognize the advantages of employing mobile portfolios as effective tools for learning and assessment to foster their students’ goal-oriented inspirational surge, encourage active participation, and provide positive feedback and clues on how to improve their learning.